Master-helper control strategy to robotic systems in tracking an object subject to environmental constraints - Gao, W.; Yao, B. (IECON' 90 : 16th annual conference of IEEE Industrial Electronics Society : November 27-30, 1990, Asilomar Conference Center, Pacific Grove, California, 1990)
A hierarchical control strategy is developed for robotic systems (multiple robot systems) holding a rigid body to track a given motion in the presence of environmental constraints. A mathematical formulation of the environmental constraints is introduced which is simple enough in many cases. The control is constructed following a master-helper control scheme in which the global controller is realized by a self-organizing algorithm. Simulations show that the tracking errors are negligibly small.< >